Pengaruh Perilaku Pemimpin dan Penilaian Kinerja Terhadap Prestasi Kerja Pegawai Pada Kantor Pertanahan Kabupaten Bekasi: The Influence of Leadership Behavior and Performance Appraisal on Employee Work Performance at the Bekasi Regency Land Office - Sonia Epilafaza; Eulin Karlina (CV Warnak Johanna Nusantara, 2025)
The Bekasi Regency Land Office is one of the institutions with a high service volume, reaching approximately 26,000 requests per month. This condition requires employees to perform optimally, making effective leadership and an objective performance appraisal system highly crucial. This study is motivated by the urgency of leadership roles and performance evaluation mechanisms in supporting productivity and achieving organizational goals. Data were collected by distributing questionnaires to 63 respondents, consisting of both PPNPN and Non-PPNPN employees. The leader behavior variable was measured using indicators such as planning, concern, development, solidarity, and tolerance. Meanwhile, performance appraisal covered work quantity, quality of results, task completion timeliness, and the objectives of the appraisal itself. The hypothesis testing results revealed that leader behavior had a t-value of 4.046 with a significance level of 0.000, while performance appraisal had a t-value of 2.728 with a significance of 0.008. The simultaneous test showed a significance value of 0.000, indicating that both variables significantly affect employee performance. The coefficient of determination (R²) was 0.608, demonstrating that 60.8% of the variation in work performance is explained jointly by the two variables. These findings indicate that effective leadership and the implementation of transparent and objective performance appraisal systems play a significant role in enhancing employee performance.